Poly(hydroxybutyrate-co-hydroxyvalerate)-based nanocomposites for antimicrobial active food packaging containing oregano essential oil. (December 2020) - da Costa, Renata C.; Daitx, Tales S.; Mauler, Raquel S.; da Silva, Natália M.; Miotto, Marília; Crespo, Janaina S.; Carli, Larissa N.
Highlights: Active packaging was developed using PHBV as a biodegradable and renewable matrix. Essential oil was combined with different clays to obtain functional properties. Addition of clay significantly improved the oxygen barrier property of the films. Clay/essential oil combination affected the release of the antimicrobial active. The antimicrobial activity of PHBV/clay/essential oil films was confirmed. Abstract: Polymer films based on poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) nanocomposites were prepared for active food packaging using oregano essential oil (OEO) as an antimicrobial agent. The films were prepared by melt blending using different clays [halloysite (Hal), kaolinite (Kaol), and sepiolite (Sep)] combined with OEO, with the aim of improving the thermal, mechanical and oxygen barrier properties of the materials. The addition of clays and OEO improved thermal stability and increased the crystallinity of the films. Depending on the clay, it is possible to achieve a suitable release rate of the antimicrobial activity in a simulant medium for aqueous foods with low pH. In all the compositions containing OEO, an inhibition effect was observed against Gram-positive and Gram-negative bacteria. Therefore, the combination of OEO and PHBV nanocomposites is a suitable alternative for the preparation of active films, improving the properties of these materials to ensure quality and extend the shelf life of foods.